Satisfaction ERP Systems: Impact on End-User - Andreas Andreas; Riska Natariasari (Indonesian Journal of Economics, Social, and Humanities, 2019)
ERP systems are integrated information systems that can be applied in both business and non-business organizations. For business organizations it covers the entire functional enterprise that includes accounting and finance, production, sales, purchasing, personnel and other functions. These functions are separated by software modules and interconnected with the integrated data center. Implementation of ERP systems does not always provide satisfaction for end-users. This paper examines the quality of information systems and service that impact on end-user satisfaction, specifically banking companies located in Pekanbaru, Indonesia. Data analysis results reveal that the information systems and service quality partially affect end-users’ satisfaction with ERP systems and thus these findings, remind the designers of ERP systems to improve the quality information systems and the availability of user friendly service.